Light and layered knits 19 sophisticated designs for every season - Square, Vicki 1954- (Loveland, CO Interweave Press, 2012)
"Best-seller Vicki Square returns, this time focusing on a lighter layered look that will appeal to knitters of all ages. Working with lighter weight yarns in fibers such as silk, linen, cotton, and bamboo, Vicki creates garments that work in all climates, that can be layered and removed at will, that are equally at home in a casual or workplace setting. These are knits that are meant to be worn every day, knits that combine polish with comfort, practicality with style. These are versatile wardrobe staples-shells, fluid tops, draped tunics, light cardigans and wrap sweaters and more. These are knits that reflect the way that women dress today. Vicki takes a holistic approach to knitting here: her goal is to offer the reader a functional, multi-purpose wardrobe, not merely a collection of individual patterns. Many garments are customizable-sleeves can be added, lengthened, or removed. Garments can be worn alone or layered over one another. She offers graphic color through intarsia, slip stitch, and stranded-knitting detail, and also shows readers how they can simplify the design by using only one or two colors instead. She offers a variety of shaping techniques (increases, decreases, gauge, and stitch patterns) to help create a garment more or less fitted, as the wearer prefers. Short-rows are also used to help shape a garment-adding volume and drape. She shows how by using a variety of yarn weights one can create visually interesting details, and make the garment lighter and more comfortable at the same time. A restrained use of ribbon, ladder, and other novelty yarns create interesting textures with little effort. Finally, techniques such as applied i-cord, 3-needle bind-off, and slip-stitch crochet seaming give the projects a polished finish. In addition to the 22 patterns, sidebars will discuss warm-weather fibers and their properties, creating texture, working with color, and stitch selection. "--
"Lighter yarns, comfortable fibers, and layered garments translate into knits to truly live in, not just projects to do"--
Machine generated contents note: Introduction -- Projects -- Keyhole -- Sport Zip Jacket -- Big Lapel Cardigan -- Renaissance -- Rolled V Collar Pullover -- Ruffle Shell -- Stacked Bracelets -- Uru Jacket -- Wrap Blouse -- Zig-Zag Top -- Peplum Shell -- Origami Flower Shell -- Long-Sleeved Tee -- Lace Collar Shell -- Lace Cardigan -- Fair Isle and Lace Tunic -- Euro Lace Tunic -- Eros Jacket -- Celtic Queen -- Big Cable Pullover -- Slip-Stitch Tee -- Confetti Tee -- Maze Tee -- Glossary -- Sources for Supplies -- Index
Includes bibliographical references (page 158) and index
1
Keywords: CRAFTS & HOBBIES / Needlework / Knitting; Knitting -- Patterns